ON KERNEL HAZARD RATE FUNCTION ESTIMATE FOR ASSOCIATED AND LEFT TRUNCATED DATA - Guessoum, Zohra; Tatachak, Abdelkader (Revstat, 2020)
* Let {[X.sub.N], N [greater than or equal to] 1} be a sequence of strictly stationary associated random variables of interest, and {[T.sub.T], N [greater than or equal to] 1} be a sequence of random truncating variables assumed to be independent from {[X.sub.N], N [greater than or equal to] 1}. In this paper, we establish the strong uniform consistency with a rate of a kernel hazard rate function estimator, when the variable of interest is subject to random left truncation under association condition. Simulation results are also provided to evaluate the finite-sample performances of the proposed estimator. Key-Words: * associated data; hazard rate function; Lynden-Bell estimator; random left truncation; strong uniform consistency rate. AMS Subject Classification: * 62G05, 62G07, 62G20.